2022
DOI: 10.1007/s12144-022-03847-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z software employees turnover intention

Abstract: This study applied the social exchange and social identity theories to investigate the association among resonant leadership, self-efficacy, organizational identification, work performance, and turnover intentions in Generation-Z (Gen-Z) software professionals. The study sampled 73 leader-subordinate dyads from 10 large-scale software companies in India through an online survey. Hierarchical linear modeling, including multilevel mediation, was conducted to test the proposed model. The results of this study rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Meanwhile, the ability to empathize, which is among the universal characteristics that a good leader should possess, improves commitment of employees to their organizations and their sense of trust and motivates Generation Z (Kasaroğlu, 2021;Gaan and Shin, 2022). From the perspective of Generation Z, a real and effective leader should show empathy, develop a friendly relationship with employees in the working environment and be humble (Singh and Dangmei, 2016;Grow and Yang, 2018;Aydoğdu and Kara Özkan, 2021;Diz, 2021;Dwidienawati et al, 2021;Demirbilek and Keser, 2022;Tidhar, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the ability to empathize, which is among the universal characteristics that a good leader should possess, improves commitment of employees to their organizations and their sense of trust and motivates Generation Z (Kasaroğlu, 2021;Gaan and Shin, 2022). From the perspective of Generation Z, a real and effective leader should show empathy, develop a friendly relationship with employees in the working environment and be humble (Singh and Dangmei, 2016;Grow and Yang, 2018;Aydoğdu and Kara Özkan, 2021;Diz, 2021;Dwidienawati et al, 2021;Demirbilek and Keser, 2022;Tidhar, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A condition for creating this awareness is empathic communication. The leader's humility affects the level of effective leadership (Poyraz and Atalay Cilveoğlu, 2020) positively, improves employees' commitment to their organizations and their sense of trust, and motivates Generation Z (Kasaroğlu, 2021;Gaan and Shin, 2022). Similarly, for the participants, empathy is necessary for communication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that Gen Z employees differ from members of Generation Y (Millennials) (born between 1980 and 1994) [ 5 , 6 , 7 ]. Generation Z workers need more structural empowerment from their leaders to perform better at work [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important that businesses discover ways to boost and improve Gen Z employees’ work performance. Furthermore, Generation Z is also more pragmatic, impatient, adaptable, braver, optimistic about the future, and has more realistic work expectations than Millennials because they do not understand the concept of struggling [ 5 , 6 , 7 ]. They constantly seek out new opportunities and motivations, and they have no fear of change [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation